Theorizing Māori-Philippine solidarities through agential realism and punk rock pedagogy. Issue 1 (May 2023) - Romero, Noah; Estellés, Marta; Grant, Wairehu
This article utilizes looks to punk rock pedagogy or the ways in which countercultural and decolonial ontologies are developed in punk subculture, to theorize Māori-Philippine relations in Aotearoa New Zealand. It uses an agential realist methodology to engage with the creative works of TOOMS, James Roque, and Marianne Infante (three New Zealand performing artists of Philippine ancestry). These works read through historiographic accounts of the Philippine diaspora to theorize how contemporary independent artists are reviving the ancestral bonds that once linked the Philippines and the Pacific. Theorizing Māori-Philippine relations through punk rock shows what Indigenous and immigrant peoples stand to gain when they decenter the colonizer and prioritize communing with one another.